Impact of Multi-modality Monitoring Using Direct Electrical Stimulation to Determine Corticospinal Tract Shift and Integrity in Tumors using the Intraoperative MRI - Krivosheya, Daria; Rao, Ganesh; Tummala, Sudhakar; Kumar, Vinodh; Suki, Dima; Bastos, Dheigo C.A.; Prabhu, Sujit S. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Introduction Preserving the integrity of the corticospinal tract (CST) while maximizing the extent of tumor resection is one of the key principles of brain tumor surgery to prevent new neurologic deficits. Our goal was to determine the impact of the use of perioperative diffusion tensor imaging (DTI) fiber-tracking protocols for location of the CSTs, in conjunction with intraoperative direct electrical stimulation (DES) on patient neurologic outcomes. The role of combining DES and CST shift in intraoperative magnetic resonance imaging (iMRI) to enhance extent of resection (EOR) has not been studied previously.Methods A total of 53 patients underwent resection of tumors adjacent to the motor gyrus and the underlying CST between June 5, 2009, and April 16, 2013. All cases were performed in the iMRI (BrainSuite 1.5 T). Preoperative DTI mapping and intraoperative cortical and subcortical DES including postoperative DTI mapping were performed in all patients. There were 32 men and 21 women with 40 high-grade gliomas (76%), 4 low-grade gliomas (8%), and 9 (17%) metastases. Thirty-four patients (64%) were newly diagnosed, and 19 (36%) had a previous resection. There were 31 (59%) right-sided and 22 (42%) left-sided tumors. Eighteen patients (34%) had a re-resection after the first intraoperative scan. Most patients had motor-only mapping, and one patient had both speech and motor mapping. Relative to the resection margin, the CST after the first iMRI was designated as having an outward shift (OS), inward shift (IS), or no shift (NS).Results A gross total resection (GTR) was achieved in 41 patients (77%), subtotal resection in 4 (7.5%), and a partial resection in 8 (15%). Eighteen patients had a re-resection, and the mean EOR increased from 84% to 95% (p = 0.002). Of the 18 patients, 7 had an IS, 8 an OS, and in 3 NS was noted. More patients in the OS group had a GTR compared with the IS or NS groups (p = 0.004). Patients were divided into four groups based on the proximity of the tumor to the CST as measured from the preoperative scan. Group 1 (32%) included patients whose tumors were 0 to 5 mm from the CST based on preoperative scans; group 2 (28%), 6 to 10 mm; group 3 (13%), 11 to 15 mm; and group 4 (26%), 16 to 20 mm, respectively. Patients in group 4 had fewer neurologic complications compared with other groups at 1 and 3 months postoperatively (p = 0.001 and p = 0.007, respectively) despite achieving a similar degree of resection (p = 0.61). Furthermore, the current of intraoperative DES was correlated to the distance of the tumor to the CST, and the regression equation showed a close linear relationship between the two parameters.Conclusions Combining information about intraoperative CST and DES in the iMRI can enhance resection in brain tumors (77% had a GTR). The relative relationship between the positions of the CST to the resection cavity can be a dynamic process that could further influence the surgeon's decision about the stimulation parameters and EOR. Also, the patients with an OS of the CST relative to the resection cavity had a GTR comparable with the other groups.
Keywords: corticospinal tract; intraoperative MRI; subcortical stimulation